Réponse :
( a ; x ) ∈ { ( -4√2 ; 2√2 - 1 ) ; ( +4√2 ; -1-2√2 ) }
Explications étape par étape :
■ x² + (a+2)x + (a+9) = 0
■ discriminant Δ = (a+2)² - 4(a+9)
= a² + 4a + 4 - 4a - 36
= a² - 32
= (a + 4√2) (a - 4√2)
■ il faut Δ nul donc a1 = -4√2 OU a2 = +4√2
■ cas a1 = -4√2 :
la racine double cherchée est alors :
x1 = (4√2 - 2)/2 = 2√2 - 1 .
■ cas a2 = 4√2 :
la racine double cherchée est alors :
x2 = -1 - 2√2 .
≈ -3,83 .
■ vérif :
x² + 7,657x + 14,657 = 0 donne bien Δ ≈ 0
d' où la racine double x2 ≈ -3,83 .